High throughput Phenotypic Microarray profiling of Mycobacterium abscessus - Ameen, Sirwan Muhsin Muhammed (Sulaimani Journal for Pure and Applied Sciences, 2018)
Mycobacterium abscessus group comprises of five species of rapidly growing mycobacteria. These mycobacteria are increasingly responsible for difficult-to treat, opportunistic cutaneous and respiratory tract infections, notably in cyctic fibrosis patients. Identification at the species level remains problematic and is relying on nucleotide sequence analyses, leaving a need for routine, phenotypic identification of such isolates. Here, the carbon and peptide nitrogen source utilization patterns of Mycobacterium abscessus complex mycobacteria was investigated using Biolog phenotype MicroArray analysis based on tetrazolium dye reduction. In a first step, a data base was built after duplicate investigation of Mycobacterium abscessus, Mycobacterium bolletii, Mycobacterium massiliense, Mycobacterium chelonae and Mycobacterium franklinii type strains. In this study, 190 carbon sources were tested; 77 (40.5%), 77 (40.5%), 77 (40.5%), 76 (40%) and 37 (19.5%) were found to be utilized by type strains of M. abscessus, M. bollettii, M. massiliense, M. chelonae and M. franklinii. Of 285 peptide nitrogen sources, they were found able to utilize 217 (76 %), 216 (75.7 %), 209 (73. 3 %), 194 (68 %) and 24 (8.4 %) nitrogen substrates, respectively. Each species yielded one specific profile, thus allowing for their unambiguous phenotypic identification at the species level. In a second step, a collection of M. abscessus, M. bolletii, M. massiliense and M. chelonae was tested to assess the usefulness of the Biolog for identification. We observed that all then identical strains were correctly identified at the species level.
Keywords: Phenotypic Microarray; rapidly growing mycobacteria